Técnicas de infusão de marcadores para a determinação do clearance ruminal de ácidos graxos voláteis - Meirelles, Fabíola da Cruz (2009)
The removal (clearance) of volatile fatty acids (VFA) from the rumen occurs by absorption through the wall of the body or passage through the rumen fluid phase to the omasum. This work was conducted in order to validate a method of incipient infusion of the liquid phase markers to digest intact by comparing with the mixing other markers of rumen digesta evacuated, which has proven. Four cows were allocated to four treatments in a split plots, aligned in a 2x2 factorial arrangement means the method of infusion of markers and diet, with two simultaneous periods of 18 days. The four combinations were: forage diet and infusion of markers to digest intact or evacuated, the diet of forage and concentrate and infusion of marker to digest intact or evacuated. Four liters of solution were added to the markers ruminal containing 56.8 grams of Cr-EDTA associated with 360 grams of valeric acid. Serial samples of rumen fluid were collected for determination of pH, concentration of VFA and chromium. The fractional clearance rate of total VFA was estimated by the exponential decay of the concentration of valerate over time. The clearance of VFA by passage to the fluid phase was estimated by a decrease in concentration of chromium over time and fractional clearance rate of absorption was estimated by difference. A biopsy was performed at the end of each period for the morphological analysis. The volume of rumen fluid was measured by the concentration of chromium at time zero, estimated by the intercept of the non-linear regression describing the drop in ruminal concentration of chromium over time and also the dry matter content and weight of rumen digesta obtained in ruminal evacuation. The fractional rates of VFA total clearance and absorption did not differ (P>0.30) between the techniques, showing that the infusion technique to digest intact is comparable to the infusion technique to digest evacuated. The fractional rate of passage of the fluid phase, however, was lower (P=0.06) when added to the digesta markers evacuated, probably reflecting the destabilization of rumen during the evacuation and homogenization of the markers and also the largest volume of fluid observed in animals with digesta evacuated. We conclude that the technique of infusion of markers to digest intact without artificial mixing is efficient for determining the clearance of ruminal VFA and has the advantage of preserving the stratification of the rumen, allowing measurements under conditions closer to physiological.